Transformasi Distingsi Madrasah Berbasis Pembelajaran Mendalam dalam Kurikulum Nasional: Evaluasi Teoretis dan Strategi Inovatif - Heri Sulistyowati, Octalia; Irsyadiyah Husna, Lathifa; Aura Nisya, Zahra; Meliani, Pipit; Haningsih, Sri (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2026)
The dynamics of changes in the National Curriculum often pose challenges for madrasahs in maintaining their distinctive identity. On one hand, madrasahs are required to be adaptive to national standards, yet on the other hand, they must preserve Islamic values as the core spirit of the institution. This study aims to theoretically evaluate the potential distinctiveness of madrasahs and formulate innovative measurement strategies within the dynamic structure of the National Curriculum. This study employs a descriptive qualitative approach with a library research design. Data processing and analysis techniques utilize content analysis and thematic analysis carried out linearly to ensure the objectivity of coding. The results indicate that theoretically, madrasah distinctiveness is deeply rooted in the integration of science and Islam, an adab-based educational orientation, and a differentiative religious curriculum. Although current curriculum policies provide room for flexibility, the risk of homogenization (uniformity) and curriculum overload remains a major conceptual challenge. As a practical solution, this study formulates an innovative curriculum evaluation strategy shifting from conventional models toward an authentic-comprehensive evaluation. This innovation is integrated through the optimization of the P5-PPRA assessment rubrics and madrasah culture quality indicators. Through a measurement navigation model that balances institutional accountability and professional responsibility (felt obligation), madrasahs can remain adaptive to the national curriculum without losing their identity. This study implies the importance of reorienting educational quality evaluation policies to be more inclusive of the distinctiveness of Islamic educational institutions.